2012
DOI: 10.1016/j.jmatprotec.2012.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Improving minimum quantity lubrication in CBN grinding using compressed air wheel cleaning

Abstract: a b s t r a c tThe application of minimum quantity lubrication (MQL) in grinding has emerged as an alternative for reducing the abundant flow of cutting fluids, thus achieving cleaner production. Although considered an innovative technique in grinding operations, its widespread application is hindered due primarily to the high heat generation and wheel pore clogging caused by machined chips, harming the final product quality and increasing tool wear on the machine. This study sought to improve MQL use in grind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 111 publications
(59 citation statements)
references
References 29 publications
0
53
0
4
Order By: Relevance
“…The air flow rate was monitored using a turbine-type meter, calibrated to a pressure of 8.0 × 10 5 Pa. Figure 2 presents the nozzle for MQL application turbulence of the air-oil mixture, enhancing penetration at the wheel/workpiece interface. A wheel cleaning system using compressed air (at a flow rate of 8.0 × 10 -3 m 3 /s and pressure of 7.0 bar) was also used 23 . The nozzle was placed at 1 mm in relation to the wheel cutting surface.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The air flow rate was monitored using a turbine-type meter, calibrated to a pressure of 8.0 × 10 5 Pa. Figure 2 presents the nozzle for MQL application turbulence of the air-oil mixture, enhancing penetration at the wheel/workpiece interface. A wheel cleaning system using compressed air (at a flow rate of 8.0 × 10 -3 m 3 /s and pressure of 7.0 bar) was also used 23 . The nozzle was placed at 1 mm in relation to the wheel cutting surface.…”
Section: Methodsmentioning
confidence: 99%
“…Recently a study was done about the use of compressed air jet for wheel cleaning, when applying MQL in grinding with CBN wheel. The results showed that an air jet incidence angle of 30º turns its penetration in the cutting zone more efficient, providing a better cleaning of the wheel, improving surface roughness, roundness errors and wheel wear, when compared to traditional MQL (without cleaning) 23 . Reduction of fluid flow associated with better results indicate that this improvement of cooling-lubrication conditions in grinding may reduce environment and health hazards, contributing to a cleaner, faster, and more cost-effective manufacturing process.…”
Section: Minimum Quantity Lubrication (Mql)mentioning
confidence: 99%
“…Assim, como há pouco fluido de corte, a peça sai praticamente limpa e permite o monitoramento visual do processo [3]. O ar carrega o óleo diretamente (com elevada velocidade) para a zona de corte, o que faz com que esse seja um método bastante eficiente de lubrificação [14]. Embora chamada também de sistema de névoa, ou ainda usinagem próxima a seco, a técnica MQL apenas aproveita a velocidade do ar para conduzir o lubrificante até o ponto desejado e não para criar uma névoa ao redor da peça.…”
Section: A Mínima Quantidade De Lubrificaçãounclassified
“…Oliveira et al [14] afirmam que a emissão acústica está relacionada com a condição do processo de retificação e com as condições da superfície do rebolo e da peça. Todos os fenômenos físicos que ocorrem no processo (atrito, deformação plástica e elástica e remoção de cavaco) podem gerar emissão acústica.…”
Section: Emissão Acústicaunclassified
“…Ta bardzo mała ilość PCS doprowadzana do strefy szlifowania pozwala w znacznym stopniu zredukować tarcie w strefie kontaktu CPS z powierzchnią obrabianą oraz ogranicza adhezję produktów szlifowania do powierzchni ściernicy [28]. Wydajne smarowanie jest zapewnione ponieważ strumień powietrza przenosi krople PCS bezpośrednio do strefy szlifowania, natomiast w przypadku obróbki z użyciem konwencjonalnej metody zalewowej należy stosować szczegól-ne procedury, aby PCS skutecznie dotarł do strefy szlifowania [29].…”
Section:  Smarowanie Z Minimalnym Wydatkiem Płynu Chło-dząco-smarująunclassified